On time-periodic solutions of some nonlinear parabolic equations with nonmonotone multivalued terms - Otani, Mitsuharu (2020)
In this paper we study the existence of time periodic solutions to a class of nonlinear parabolic equations with multivalued nonlinear terms subject to the homogeneous Dirichlet boundary condition. We give two types of existence results: one for large periodic solutions with any large data, and the other for small periodic solutions with small data. Both concern the case where the nonlinear terms contain either a upper semi- continuous multivalued term or a lower semicontinuous multivalued term. Some applications of our results are also given.